The challenges to library learning [ solutions for librarians - Massis, Bruce E. (New York : Routledge, 2008)
Offers a practical philosophy of engagement that can be used to meet the challenges facing librarians, including staffing shortages, depleted or eliminated training budgets, longer hours, greater
1. The rules of engagement -- 2. E-learning for library staff -- 3. Developing a personal learning plan -- 4. The substitute librarian : providing a mechanism for the library learner to learn -- 5. Marketing your library learning program to staff -- 6. The community of learning program for library staff : the SEFLIN case study -- 7. Teaching and measuring information literacy training
Description based on print version record
Includes bibliographical references (p. 87-98) and index
Keywords: Employee motivation; Librarians -- In-service training; Library education (Continuing education); Library employees -- In-service training; Library personnel management